(untitled) (Research, Society and Development, 2020)
This study was carried out to evaluate the microbiological quality of salmon and tuna based sashimi marketed in the city of Fortaleza-CE. Eight samples were collected from six types of retail outlets comprising restaurant, kiosk at the shopping mall, supermarket and food truck. The samples were submitted to the counts for total aerobic mesophilic bacteria by the spread plate technique, coliforms enumeration at 35 °C and 45 °C (MPN.g-1) and the direct-plate count method for the enumeration of Staphylococcus aureus. The samples collected from kiosks at the shopping mall showed the highest counts for total aerobic mesophilic in salmon sashimi, coliforms at 35 °C in tuna sashimi and coliforms at 45 °C in both types of sashimi. The highest count for coliforms at 35 °C was in the restaurant. In the analyzes carried out for the count of Staphylococcus aureus was observed that the levels were considered acceptable of current regulation. All samples of sashimi are in compliance with the legislation in force, however, there was a high count of total aerobic mesophilic bacteria and coliforms at 35 °C. Given this, it is suggested that the samples studied may be associated with failures in the control of time and temperature of fish storage, showing the importance in quality control of the type of food without any additional process before consumption.